2013
DOI: 10.1097/prs.0b013e3182910a82
|View full text |Cite
|
Sign up to set email alerts
|

Fat Grafts Supplemented with Adipose-Derived Stromal Cells in the Rehabilitation of Patients with Craniofacial Microsomia

Abstract: Therapeutic, II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
99
0
12

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(111 citation statements)
references
References 43 publications
0
99
0
12
Order By: Relevance
“…A study of 14 patients showed that this method may be safe and effective, and even superior in clinical application to standard lipoinjection. The surviving fat volume at 6 months was 88% for the experimental group (CAL) and 54% for the control group (conventional lipoinjection) [39].…”
Section: Cosmetic Surgerymentioning
confidence: 99%
“…A study of 14 patients showed that this method may be safe and effective, and even superior in clinical application to standard lipoinjection. The surviving fat volume at 6 months was 88% for the experimental group (CAL) and 54% for the control group (conventional lipoinjection) [39].…”
Section: Cosmetic Surgerymentioning
confidence: 99%
“…Chang and colleagues 23 reported a volumetric analysis of SVF-supplemented fat grafting and regular fat grafting to progressive hemifacial atrophy patients, concluding that fat survival and clinical improvement was greater with SVFsupplemented grafting than fat grafting alone after 6 months. Tanikawa and colleagues 24 reported that SVF-supplemented fat grafting for patients with craniofacial microsomia was effective. Survival fat volume was 88% at 6 months, which was significantly greater that nonsupplemented fat grafting (54%).…”
Section: Clinical Reports Of Cell-assisted Lipotransfermentioning
confidence: 98%
“…[42] Yine ya¤ kaynaklı MKH'lerin çalııldı¤ı bir baka çalımada geni keratokist nedenli hemimaksillektomi uygulanan bir hastada GMP koullarında hazırlanmı kök hücre ile trikalsiyum fosfat granüllerini titanyum mesh içinde prefabrike edilmi ve elde edilen dokunun mikrovasküler flep olarak maksillaya nakli sa¤lanmı doku biyopsilerinde yeniden ekillenen kemik varlı¤ının tespit edildi¤i bildirilmitir. [43] Tanikawa ve ark.nın [44] 2013 yılında yaptıkları klinik çalımalarında; 14 adet kraniyofasiyal mikrozomili hastaya karakterizasyonu sa¤lanmı ve canlı hücre sayısı hesaplanmı otolog YD-MKH'li ve kök hücresiz kontrol grubu olarak greft uygulanmıtır. Çalımada izolasyon sonrası CD73 ve CD105 ekspresyonları %95 olarak tespit edilirken kök hücre uygulanan gruptaki hastalarda ya¤ volümü sa¤kalımı %88, kontrol grubunda ise %54 oranında tespit edilmitir.…”
Section: Self-renewal (Kendini Yenileyebilme)unclassified
“…Çalımada izolasyon sonrası CD73 ve CD105 ekspresyonları %95 olarak tespit edilirken kök hücre uygulanan gruptaki hastalarda ya¤ volümü sa¤kalımı %88, kontrol grubunda ise %54 oranında tespit edilmitir. [44] Kardiyak hastalıklarda, MKH'lerin kullanımı, bilinen en eski kullanım alanlarından biridir. ‹skemik kalp hastalıklarında umut kayna¤ı olan MKH'ler geni randomize ve uzun dönemli klinik çalımalara ihtiyaç duymaktadır.…”
Section: Self-renewal (Kendini Yenileyebilme)unclassified